A Case of Familial Hypocalciuric Hypercalcemia (Bangladesh Journal of Otorhinolaryngology, 2023)
Background: Primary hyperparathyroidism (PHPT) is a common endocrine disorder that is the leading benign cause of hypercalcemia. It may occur due to autonomous hypersecretion of parathyroid hormone (PTH), independently of serum calcium levels. Familial hypocalciuric hypercalcemia (FHH) is a group of autosomal dominant rare genetic diseases only affecting the regulation of calcium metabolism. It is usually caused by one of many heterozygous missense mutations in the calcium-sensing receptor (CaSR) gene, which could up-regulate the set point of parathyroid cells. When the CaSR receptor is inactivated, PTH is not suppressed despite relatively high calcium, which makes FHH similar to PHPT. We present a unique case of concomitant FHH and suspected parathyroid adenoma.Case summary: A 10-year-old girl with symptomatic severe hypercalcemia, high PTH, and genetically diagnosed as FHH was referred to the department of otolaryngologyhead and neck surgery due to surgical excision of suspected parathyroid adenoma. Her biochemical evaluation showed elevated serum calcium and PTH. The calcium– creatinine clearance ratio was >0.01 (0.16). Her parathyroid scintigraphy showed negative for parathyroid adenoma, but the ultrasonography of the neck revealed an enlarged right inferior parathyroid gland. She underwent surgical excision of both the right superior and inferior parathyroid glands. However, the patient’s serum calcium and parathyroid hormone increased in the postoperative period, and her symptoms remained unchanged.Conclusion: The correct diagnosis of the underlying cause of hypercalcemia is essential to ensure the proper treatment. Patients with FHH should avoid operative treatment, and PHPT should be differentiated to determine whether surgery should include parathyroidectomy with the removal of suspected parathyroid adenoma.Bangladesh J Otorhinolaryngol 2023; 29(1): 39-44